Die Fehlbewertung durch das Stuttgarter Verfahren: eine Sensitivitätsanalyse der Werttreiber von Steuer- und Marktwerten - Jens Müller (Arbeitskreis Quantitative Steuerlehre (arqus), 2007)
This paper focuses on firm valuation for tax purposes of non-listed company shares and its sensitivity towards different market conditions. Since the value of a private company cannot be observed on the stock market the value has to be estimated. Due to uncertainty, expected future profits may not serve as a tax base. Therefore, in Germany e.g., a tax value is derived on the basis of a combination of net assets and historic profits - the so called Stuttgart Method. A Discounted Cash Flow Model, as a generally accepted method of firm valuation, is used as a proxy for the market value. In this analysis a simulation quantifies the gap between both approaches for firms of six different industries. Thereby, we find out which industries are discriminated and which are subsidized by taxation. Furthermore, the sensitivity of the value gap with regard to the relevant value drivers (cost of capital, financial structure, corporate tax rates, growth, and timing effects) is investigated. In the basic setting the value is only 31,3% to 92,4% of the market value. Thus, tax values lead to a severe undervaluation of the company. Moreover, the span of the relations shows that the firms are treated unequally. Variations show that overvaluations are also likely to be observed. These results are helpful to design a true and fair tax base.
Keywords: G12; H29; 330; firm valuation; gift tax; inheritance tax; tax value; sensitivity analysis; value gap; discounted cash flow; Steuerbemessung; Erbschaftsteuer; Unternehmensbewertung; Sensitivitätsanalyse; Kritik; Theorie; Deutschland